Geoelectric prospection of copper occurrence in folded structures in the sul-riograndense shield (Brazil) - dos Santos, Shaiely Fernandes; Moreira, Cesar Augusto [UNESP]; Rosa, Fernanda Teles Gomes [UNESP]; Borssatto, Karolinny [UNESP]; da Silva, Marly Aparecida [UNESP] (Sociedade Brasileira de Geofisica, 2018)
Sulfide prospecting with electrical resistivity and induced polarization geophysical methods are effective due to the contrast of electrical resistivity and chargeability disseminated sulfides or filonean deposits, which are characterized by low resistivity and high polarizability. This work carried out an electrical tomographic acquisition in a copper mineral occurrence, in the region of Caçapava do Sul, Rio Grande do Sul State, Brazil. Three lines were acquired using a dipole-dipole arrangement, with a length of 400 m and a spacing of 5 m between the electrodes. The lines were surveyed perpendicularly to a large anticlinal ridge, where carbonate and copper sulfides were recognized in a past mineral exploration galleries. The 2D inversion models and 3D multilevel maps indicate central and lateral regions with high resistivity and chargeability indicating the probable presence of copper sulfides, possibly in quartz veins. Peripheral zones with moderate resistivity and chargeability suggest zones of argilization; high chargeability and low resistivity are likely zones of sulfation; and high resistivity and low chargeability are possible zones of silicification.
Keywords: 3D multilevel modeling; Chargeability; Mineral research; Resistivity; Sulfide